Trois villages d' Epire (1958/61-1988): eléments d'analyse socio-démographique - Damianakos, Stathis; Kassimis, Babis; Maropoulou, Marina; Zacopoulou, Ersi (The Greek Review of Social Research, 1990)
[Δε διατίθεται περίληψη / no abstract available]